Sphingomyelin synthase 2 deficiency inhibits the induction of murine colitis‐associated colon cancer. Issue 9 (19th September 2017) - Ohnishi, Toshio; Hashizume, Chieko; Taniguchi, Makoto; Furumoto, Hidehiro; Han, Jia; Gao, Rongfen; Kinami, Shinichi; Kosaka, Takeo; Okazaki, Toshiro
ABSTRACT: Sphingomyelin synthase 2 (SMS2) is the synthetic enzyme of sphingomyelin (SM), which regulates membrane fluidity and microdomain structure. SMS2 plays a role in LPS‐induced lung injury and inflammation; however, its role in inflammation‐mediated tumorigenesis is unclear. We investigated the effect of SMS2 deficiency on dextran sodium sulfate (DSS)–induced murine colitis and found inhibition of DSS‐induced inflammation in SMS2‐deficient (SMS2 −/− ) mice. DSS treatment induced a significant increase in ceramide levels, with a decrease of SM levels in SMS2 −/− colon tissue, and demonstrated attenuation of the elevation of both inflammation‐related gene expression and proinflammatory cytokines and chemokines, leukocyte infiltration, and MAPK and signal transducer and activator of transcription 3 activation. After undergoing transplantation of wild‐type bone marrow, SMS2 −/− mice also exhibited inhibition of DSS‐induced inflammation in the colon, which suggested that SMS2 deficiency in bone marrow–derived immune cells was not involved in the inhibition of colitis. Finally, in an azoxymethane/DSS‐induced cancer model, SMS2 deficiency significantly decreased tumor incidence in the colon. Our results demonstrate that SMS2 deficiency inhibits DSS‐induced colitis and subsequent colitis‐associated colon cancer via inhibition of colon epithelial cell–mediated inflammation; therefore, inhibition of SMS2 may be a potential therapeutic target for human colitis and colorectal cancer.—Ohnishi, T., Hashizume, C., Taniguchi, M., Furumoto, H., Han, J., Gao, R., Kinami, S., Kosaka, T., Okazaki, T. Sphingomyelin synthase 2 deficiency inhibits the induction of murine colitis‐associated colon cancer. FASEB J. 31, 3816–3830 (2017). www.fasebj.org —Ohnishi, Toshio, Hashizume, Chieko, Taniguchi, Makoto, Furumoto, Hidehiro, Han, Jia, Gao, Rongfen, Kinami, Shinichi, Kosaka, Takeo, Okazaki, Toshiro Sphingomyelin synthase 2 deficiency inhibits the induction of murine colitis‐associated colon cancer. FASEB J. 31, 3816–3830 (2017)